Peran UMKM dalam Meningkatkan Kesejahteraan Perekonomian di Indonesia - Evi Sirait; Bagus Hari Sugiharto; Jenal Abidin; Nely Salu Padang; Johni Eka Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the role of MSMEs in improving economic prosperity in Indonesia. This research approach collects data through literature studies, which involves reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this research are that micro, small and medium enterprises (MSMEs) are a very crucial sector for economic prosperity in Indonesia. This is because MSMEs play an important role in absorbing labor, increasing people's income, creating new business opportunities, increasing economic equality, and preserving local culture and wisdom. Apart from that, MSMEs also play an important role in creating jobs, increasing local economic growth, increasing innovation and creativity, stimulating local economic growth, economic diversification, as well as contributing to taxes and state revenues. This can improve economic prosperity in Indonesia. The indicators for measuring the level of welfare are income, housing and settlement, education and health.